In vitro assessment of ligninolytic and cellulolytic activities for 14 Agaricomycetes species, new to Bryansk Oblast (European Russia) - Volobuev, Sergey V. (Вестник Томского государственного университета. Биология)
Xylotrophic basidiomycete fungi take a unique place in the functional structure of forest ecosystems because, on the one hand, they possess an extensive complex of enzymes involved in lignin modification and degradation, and, on the other hand, they synthesize enzymes capable of cellulose decomposition. Two groups of wood-destroying fungi are widely known in this respect – brown-rot fungi producing cellulolytic enzymes and white-rot fungi possessing not only cellulases but also ligninolytic oxidative enzymes. Currently, the physiology, biochemistry and genetics of basidial fungi are being actively researched. Thanks to the intensive development of bioinformatics resources, the transcriptomes, proteomes and secretomes of higher fungi are being analysed. At all three levels, both the biochemical mechanisms of degradation of different wood types by basidiomycetes are being studied and the spectrum of enzymes of the lignocellulolytic complex involved in these processes is being revealed. However, despite the identified general regularities, the specific mechanism of wood degradation is determined by individual peculiarities of fungal enzyme systems engaged in this process. The demand for lignocellulolytic complex enzymes for biotechnology purposes continues to grow steadily, since in addition to their ability to modify complex organic polymers, these enzymes break down a wide range of substrates of both natural and anthropogenic origin. New biotechnologically promising producers of ligninases and cellulases with high biodegradation potential are constantly searched for. In this work, we present data on 14 species of xylotrophic basidiomycete fungi new to Bryansk Oblast, including little-known species Conferticium ravum, Phlebia tremelloidea, Physisporinus crocatus, with information on woody substrates and habitats occupied within the territory of the Bryanskiy Les State Nature Reserve, as well as data on general distribution and finds of these species in adjacent regions. Among hosts for revealed species of wood-inhabiting fungi, the main forest-forming trees such as Betula pendula, Picea abies, Pinus sylvestris, Populus tremula, and Quercus robur are noted. The majority of fungal cultures are obtained from basidiospores and basidiomata grown on coniferous wood. Herbarium specimens of the identified species are catalogued and stored in the Mycological Herbarium of the Komarov Botanical Institute RAS (LE), and fungal strains are deposited in the Komarov Botanical Institute Basidiomycetes Culture Collection (LE-BIN, St. Petersburg, Russia). All collected specimens and pure cultures of studied aphyllophoroid fungi are determined and verified based on both microscopic features and molecular genetic data. Physiological and biochemical characterization, including assessment of their growth rate and detection of enzymatic activity by rapid screening, was given for 16 strains of wood-dwelling fungi. The linear growth rate was measured by culturing pure cultures on standard MEA medium. The activities of ligninolytic and cellulolytic enzyme complexes were registered using the application method that is widely applied for the primary biochemical screening of strains in many culture collections worldwide. The agarized medium containing ABTS (2,2’-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid) was used for detection of oxidative enzyme activity while the cellulase activity was studied on the agarized medium with CMC (carboxymethyl cellulose). The strain LE-BIN 4006 of Phlebia tremelloidea showed high ligninolytic and cellulolytic potential and rapid colony growth rate. This strain can be recommended for further biotechnological applications. The strains LE-BIN 4422 of Emmia latemarginata and LEBIN 3999 of Phanerochaete livescens demonstrated high cellulolytic complex enzyme activity despite the detected medium colony growth rate and medium oxidative enzyme activity. Thus, based on the screening results, three strains of fungi belonging to the order Polyporales have been identified as being of practical interest for use in biotechnological delignification and remediation processes. The importance of screening studies on active enzymatic producers among not only widespread taxa, but also by including rare and little-collected species of fungi are demonstrated.